2024 Cando Economic Developer of the Year Award Winner: Community Category Bearspaw First Nation - Shotclose, Robert (Journal of Aboriginal Economic Development, 2025)
Bearspaw First Nation has accomplished so much in the field of Indigenous economic development through Rob Shotclose’s leadership and the visionary work of his Nation.